Level of knowledge, stress and acceptance of illness in young adults with type 1 diabetes mellitus - Stefanowicz-Bielska, Anna; Rąpała, Małgorzata; Mazuryk, Kamila; Dygaszewicz, Ewa (Frontiers in Endocrinology, 2025)
IntroductionThe chronic character of Type 1 Diabetes Mellitus (T1DM) causes patients to be fully aware of the essence and consequences of their illness and to suffer from stigmatisation, tiredness, stress, fear, anxiety and poor mental health.Purpose of the paperThe purpose of this paper is to assess the level of knowledge, stress and acceptance of the illness in young adults with T1DM and to present the impact of various sociodemographic and medical factors on the level of knowledge, stress and acceptance of the illness in young adults with T1DM.Materials and methodsThis study used an original survey and the psychological PSS-10 and AIS questionnaires among young adults with T1DM who had been ill for more than a year. The survey was conducted from 01.08.2023 to 30.11.2024.ResultsThe survey involved 274 young adults aged 18 to 35 years, who had T1DM for 13.4 ± 7.1 years on average. The medians of the test and raw scores for the respondents’ answers to statements in the AIS psychological questionnaire were 18 (17÷19) and 29 (23÷35), respectively, whereas the medians of the raw score and sten scores in the responses given in the PSS-10 psychological questionnaire were 20 (15÷24) and 7 (5÷8), respectively. A negative relationship was confirmed between the level of knowledge and the HbA1c concentration. The survey indicated that women with primary education, being in a relationship, smoking, having hypertension, hypothyroidism and lipohypertrophy, and being treated with multiple daily injections (MDI; automatic insulin pen) had high stress levels. There was a positive relationship between the level of stress experienced by the respondents and their BMI, as well as between the duration of the illness and the number of hyperglycaemic incidents at night. The survey indicated that people with primary education, being single, nonsmoking, not keeping a “paper” self-monitoring journal and having regular nursing and educational appointments at the Diabetes Clinic better accept their illness. The survey confirmed a negative relationship between the level of acceptance of the illness and the HbA1c concentration and hyperglycaemic incidents during the day.ConclusionsThe level of stress experienced by young T1DM patients is high. Young T1DM patients do not accept the illness. Understanding treatment principles helps patients achieve metabolic balance in a significant way. The level of stress, the level of acceptance of the illness doesn’t have relation to the level of knowledge. Contemporary technologies used in T1DM self-monitoring and treatment reduce the level of stress and help patients accept and adapt to the illness. The use of MDI generates a high level of stress in young T1DM patients, and the fact that they do not need to keep a “paper” self-monitoring journal helps them better accept the illness. Educational nurses support young T1DM patients in diabetes therapy and help them accept their illness. Young adults with T1DM need support of psychologists.